FUNGSI DAN KEWENANGAN BADAN PERTANAHAN NASIONAL TERHADAP SENGKETA TANAH YANG BELUM DIDAFTARKAN - Robyatul Adawiyah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT         One problem that needs to be our common concern to date is the issue of land has not been registered notch ratings sourced from indigenous lands, especially after the birth of the UUPA. Land has not been registered are soil derived from indigenous lands or other lands that have not been converted into one of the ground certain rights (property rights, right to build, right to life, the right to cultivate) and have not been registered or certified Office local land.Formal juridical Land Office does not have authority over land dispute has not been registered, but by the Land Office itself is still possible to carry out mediation. Mediation of land disputes has not been registered as a tangible implemented the basic tasks and functions as well as the vision and mission of the National Land Agency. Mediation is a dispute resolution that matches the character, the personality, and the way of life of Indonesian society that is familial. Advice from the author of: 1) adding the HR (human resources) in the disputes, conflicts, and cases in the Land Office; 2) Providing training and courses (training) to the mediator or mediators prospective land disputes in the Land Office; 3) Land Office to work even harder to implement socialization of land registration, this is done as a preventative measure to address land disputes has not been registered.Keywords: role of the Office of Land, Soil Not Registered.